Clinical Audit to Evaluate the Quality of GP Letters From Psychiatry Clinic at TEWV NHS Foundation Trust - Roseline Bennet Ataria; Samuel Fayomi; Harsyini Sugumaran; Clare Morgans; Susan Podmore (BJPsych Open, 2025)
Aims: This audit aims to evaluate the quality of review letters from Psychiatry clinics against standardized practices in clinical communication with General Practices (GPs). The evaluation is based on the guidelines issued by the Royal College of Psychiatrists regarding GP letters in January 2021.